Mean Size of the Landed Catch: A Fishery Community Index for Trend Assessment in Exploited Marine Ecosystems - Leitão, Francisco (Frontiers in Marine Science, 2019)
Based on fisheries landings data I propose the size-base index (community level) Mean Size of the Landing Catch (MSL). The MSL index was estimated based on i) high taxonomic resolution data available from auctions (species level), ii) demographic data acquired during auction, namely species landed by “size-box” categories, which is mandatory to be assessed in all EU members state for fisheries quality and statistic proposes. The MSL was calculated from the average inferred size-box categories of a species weighted by their annual catch. The use of MSL allows determining inter-annual changes in the size of the catch when weighted data is available from the fishery. Using the Portuguese fisheries landing data as an example, the MSL revealed that the landing yield of large fish linearly declined over time while the catch of small fishes increased (i.e. survivors to old age was reduced by fishing). The MSL can be easily used to assess trends in marine exploited commercial communities (community rather than population level) and is fully applicable with any species-size data source (e.g. scientific surveys, visual census data). The MSL can also be used as a key indicator within the new ecosystem-based Marine Policy Framework Strategy (ecosystem approach to fisheries), which required the use of size-based indicators for the assessment of fisheries trends in exploited marine communities.